2022
DOI: 10.21608/ejnsr.2022.212573
|View full text |Cite
|
Sign up to set email alerts
|

Online Teaching Readiness, Challenges and Satisfaction as Perceived by Nursing Faculty Members during COVID -19 Pandemics

Abstract: Background: Faculty members must be prepared to teach online as a strategy during the current COVID-19 epidemic. There is a rising demand and necessity for online teaching at higher education institutions. A crucial success factor for online education is the government's proactive efforts in analyzing educator readiness, problems, and satisfaction. Aim: the present study aimed to assess online teaching readiness, challenges and satisfaction as perceived by nursing faculty members during COVID -19 pandemics. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…Some respondents also had to buy internet quota with personal funds since the institution did not provide internet network. This is similar to several previous studies revealing that poor internet connections, lack of technology, infrastructure, and technical assistances were the most common problems faced by lecturers during online learning (Elewa & Mohamed, 2022;Rosalina et al, 2020).…”
Section: Resultssupporting
confidence: 91%
“…Some respondents also had to buy internet quota with personal funds since the institution did not provide internet network. This is similar to several previous studies revealing that poor internet connections, lack of technology, infrastructure, and technical assistances were the most common problems faced by lecturers during online learning (Elewa & Mohamed, 2022;Rosalina et al, 2020).…”
Section: Resultssupporting
confidence: 91%
“…Sadeghzadeh's study showed that nursing students were moderately satisfied with virtual training [33]. In a study conducted by Elewa et al during the COVID-19 pandemic, the students' satisfaction level with virtual training was reported moderate [35]. In the studies conducted by Farsi et al [36] and Ruiz-Grao et al [37], the satisfaction level with virtual training was also moderate.…”
Section: Discussionmentioning
confidence: 96%
“…This can be explained by a lack of training, support, and teaching resources that were available to university teachers in assisting them with a transition to online modes of teaching. There is evidence for this in rich and poor countries alike, such as in Australia (Dodo-Balu, 2017 , 2018 , 2022 ), Bangladesh (Saha et al, 2022 ), China (Liu et al, 2022 ; Tsegay et al, 2022 ), Egypt (Elewa et al, 2022 ), Japan (Kita et al, 2022 ), Pakistan (Shahid et al, 2022 ; Yasmin, 2022 ), Sweden (Hietanen and Svedholm-Häkkinen, 2023 ), Vietnam (Nguyen et al, 2022 ), and the United States (Sessions et al, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%